Window to the world exhibit installation - Unidentified photographer (Colorado State University. Libraries, 2009)
Photograph of Window to the World spring 2009 exhibit installation. People identified as guest exhibit designer and preparatory, Jack Townes, Curator, Linda Carlson, and Collections Manager, Megan Osborne, are working on the installation.
Keywords: Fashion -- History; Fashion -- Exhibitions